Eksistensi Jiwa Sebagai Fondasi Kesehatan Mental: Membaca Kembali Filsafat Islam - Ernita Dewi (Al-Widad, 2026)
The advancement of science, technology, and digitalization has brought various conveniences that are expected to improve human quality of life, including mental health. Such progress should contribute to a balance between material well-being and inner peace. However, contemporary society is witnessing an increasing prevalence of mental health problems, including stress, anxiety, depression, and a crisis of meaning. This phenomenon indicates that mental health approaches focusing primarily on biological and psychological dimensions have not fully addressed the spiritual needs of human beings. This article aims to re-examine the concept of the soul from the perspective of Islamic philosophy, analyze its relationship with contemporary mental health crises, and explain the relevance of spiritual approaches in promoting sustainable mental well-being. This study employs a library research design using a qualitative-philosophical approach. Data were collected from the works of Muslim philosophers and relevant scholarly literature and were analyzed through content analysis and critical interpretation. The findings reveal that the concept of the soul in Islamic philosophy provides a significant framework for understanding the roots of modern mental health crises, which stem from the imbalance between material and spiritual needs. The cultivation of the soul through self-discipline, purification of the heart, moral development, and Sufi practices contributes to inner tranquility, psychological resilience, and a meaningful life.